Latin American and Caribbean Regional Plan of Action on Human Settlements (UN ECLAC SantiagoUS, 1996)
Deals with aspects such as achieving social equity and alleviating urban poverty; the productivity of human settlements for improving the quality of life; improving the environment in human settlements; governability and participation; and, policy and management efficiency.
DC